Mobilizing Urban Infrastructure Finance Within A Responsible Fiscal Framework : South African Case - van Ryneveld, Philip (The World Bank, 2006)
Since South Africa held its first democratic elections in 1994, it has given significant attention to building an effective system of decentralization including provincial and local government. While provincial governments are responsible mainly for the implementation of social services such as health and education, the provision of much of the urban infrastructure is the responsibility of local government. Although many challenges remain, the country has made significant progress over the past decade in addressing urban service backlogs in poor areas. At the same time, it has greatly improved macroeconomic fundamentals. The system of financing local government seeks to place accountability firmly at the local level, with most revenues in the larger urban centers raised locally through a combination of local taxes and fees for services, while poorer regions are predominantly grant funded. The objective has been to encourage the financing of capital infrastructure through local borrowing based on sustainable, transparent local finances rather than national repayment guarantees, which are outlawed. There is some indirect subsidization of loans through the state-owned Development Bank of Southern Africa. But the emphasis is on achieving redistribution through transparent, formula-based grants paid directly from national to local governments. While further bedding down of the system is needed, the approach is proving largely successful. The paper concludes by recommending that the existing division between provinces as providers of social services and local governments as the key locus of responsibility for services related to the built environment should be strengthened, particularly through the devolution of more urban transport related functions. A number of key risks are also highlighted, including issues related to the reform of local business taxes